Factors Associated with Anxiety among Nurses and Midwives during the Covid-19 Pandemic in the Emergency Unit and Polyclinic of the Mangusada Regional Hospital, Badung Regency - I Ketut Swarjana; I Nengah Suarmayasa; Ni Nyoman Darmini; Putu Ayu Utami Dewantari; Ni Wayan Niwiraga; Ni Made Arie Dwijayanti; Ni Luh Putu Ary Swandani; Ni Luh Eka Purnamasari; Ni Luh Tia Risna Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
ABSTRACT Introduction: The Covid-19 pandemic has had a wide impact on society, including healthcare workers on the frontline dealing with Covid-19. The large number of healthcare workers who have been exposed to and died due to Covid-19 causes anxiety for both nurses and midwives who work in hospitals. Objective: This study aimed to assess the factors associated with anxiety among nurses and midwives in the emergency unit and outpatient department of Mangusada Regional Hospital. Methods: This study used a cross-sectional design involving 95 samples consisting of nurses and midwives working in the emergency unit and the outpatient department of Mangusada Regional Hospital which was selected using a total sampling technique. Data were collected using a questionnaire developed by the researchers. Furthermore, data collection was done online using a Google form that has been shared with respondents. Furthermore, the data were analyzed using univariate, bivariate, and multivariate analysis. Results: Of the total 95 respondents, 21 (22.1%) respondents experienced anxiety. Furthermore, multivariate analysis found that family history of exposure to Covid-19 (AOR: 19.39), history of comorbidities (AOR: 10.73), and support from family, colleagues, and superiors (AOR: 7.87) were significantly associated with anxiety among nurses and midwives during the Covid-19 pandemic. Conclusion: Hospital management needs to pay special attention to minimizing the anxiety experienced by nurses and midwives during the Covid-19 pandemic through the provision of social support from family, colleagues, and superiors.